Technology in Canada Through the Lens of Labour History - Lutz, John (Scientia Canadensis, 1991)
ABSTRACTThis is an extended review essay which examines contributions of recent labour history to the history of Canadian technology. It argues that three recent books: Heron's Working in Steel, Sager's Seafaring Labour, and Parr's Gender of Breadwinners have bridged the longstanding gap between the two sub-disciplines. The review suggests some future directions for a more 'complete' history of technology which incorporates both the social and technical aspects of production.